Financial monitoring and corruption: legal correlation - А R Batyaeva (RUDN Journal of Law, 2009)
This article is devoted to necessity to consider the counteraction of corruption as one of the object of the financial monitoring. The author proposes some practical recommendations how to realise it in the applicable Russian legislation. The article describes the foreign experience of corruption counteraction within anti money laundering and terrorist financing measures.